Examining the Nutrition, Oral Mucositis, and Gastrointestinal System Symptoms of Intensive Care Units Patients Receiving Enteral and Parenteral Nutrition - Ünal Aslan, Kevser Sevgi (Turkish Journal of Gastroenterology, 2023)
Background: This descriptive study aims to examine the complications that might develop in patients who receive enteral or parenteral nutrition treatment in intensive care unit in this process and to examine the nutritional status, oral mucositis, and gastrointestinal system symptoms among patients who receive enteral or parenteral nutrition treatment in intensive care unit. Materials and Methods: A sample of this study consists of 104 patients who received enteral or parenteral nutrition treatment in intensive care units between January and June 2019. The data were collected face to face by using Sociodemographic Form, constipation severity scale, Mini Nutritional Assessment Scale, Mucositis Assessment Scale, visual analog scale, and gastrointestinal system Symptoms Scale. The results were calculated as numbers, percentage, SD, and mean values. Results: Among the participating patients, 67.4% were older than 65 years, 55.8% were female, 42.3% were receiving treatment in internal medicine intensive care units, and 43.4% had severe mucositis. It was determined that 31.7% of the patients receiving treatment in intensive care units required nutrition treatment. It was determined that patients receiving parenteral nutrition had more symptoms such as gastrointestinal system symptoms, mucositis, constipation, and colonic inertia. Conclusions: It was determined that when compared to the patients receiving enteral nutrition, the patients receiving parenteral nutrition had higher scores in mucositis, visual analog scale pain, Mini Nutritional Assessment Test, constipation, obstructive defecation, colonic inertia, and gastrointestinal symptom total scores. Cite this article as: Ünal Aslan KS. Examining the nutrition, oral mucositis, and gastrointestinal system symptoms of intensive care units patients receiving enteral and parenteral nutrition. Turk J Gastroenterol. 2023;34(8):813-821.